Effective demand in the recent evolution of the US economy - Julio López-Gallardo; Luis Reyes-Ortiz (Levy Economics Institute of Bard College, 2011)
We present strong empirical evidence favoring the role of effective demand in the US economy, in the spirit of Keynes and Kalecki. Our inference comes from a statistically well-specified VAR model constructed on a quarterly basis from 1980 to 2008. US output is our variable of interest, and it depends (in our specification) on (1) the wage share, (2) OECD GDP, (3) taxes on corporate income, (4) other budget revenues, (5) credit, and the (6) interest rate. The first variable was included in order to know whether the economy under study is wage led or profit led. The second represents demand from abroad. The third and fourth make up total government expenditure and our arguments regarding these are based on Kalecki's analysis of fiscal policy. The last two variables are analyzed in the context of Keynes's monetary economics. Our results indicate that expansionary monetary, fiscal, and income policies favor higher aggregate demand in the United States.
Keywords: C52; E12; E25; E52; E63; 330; effective demand; wage shares; monetary policy; fiscal policy; model evaluation